2013
DOI: 10.1038/bjc.2013.718
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nomogram for the identification of lymph node metastasis in early cervical cancer

Abstract: Background:The objective of this study is to construct a preoperative nomogram predicting lymph node metastasis (LNM) in early-cervical cancer patients.Methods:Between 2009 and 2012, 493 early-cervical cancer patients received hysterectomy and pelvic/para-aortic lymphadenectomy. Patients who were diagnosed during 2009–2010 were assigned to a model-development cohort (n=304) and the others were assigned to a validation cohort (n=189). A multivariate logistic model was created from preoperative clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
6
42
0
Order By: Relevance
“…In support of this, a robust model, which accurately identified patients with early cervical cancer at low risk for nodal metastases, has been recently developed and validated. 22 It is of note that 3 (23%) of 13 patients were incorrectly classified as low risk by our regression model. In another study, low risk has been defined as a predicted probability of developing nodal metastasis of 5%.…”
Section: Discussionmentioning
confidence: 78%
“…In support of this, a robust model, which accurately identified patients with early cervical cancer at low risk for nodal metastases, has been recently developed and validated. 22 It is of note that 3 (23%) of 13 patients were incorrectly classified as low risk by our regression model. In another study, low risk has been defined as a predicted probability of developing nodal metastasis of 5%.…”
Section: Discussionmentioning
confidence: 78%
“…The structure of both reviews has elements in common with the one presented here and with the proposal found in the Cochrane manual of systematic reviews of interventions [ 38 ]. Other works present validation analyses of prognostic models in patients with early cervical cancer [ 39 ], LACC [ 17 ], and disseminated cancer [ 40 ]. However, only an independent external validation study of 2 predictive models in patients with LACC performed in different population was published [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Introducing universally accepted standardised FSE protocols and ensuring reporting by specialist pathologists have been shown to improve FSE accuracy [ 15 ]. Provided that FSE accuracy is satisfactory, identification of patients at low risk for nodal metastases may theoretically help inform selected patients in the absence of enlarged lymph nodes or SLNs towards less aggressive surgical interventions and reduce the lymphadenectomy-related morbidity [ 16 ]. Implementation of FSE with ultrastaging may prove cost-effective in high risk patients with respect to avoiding morbidity and should be explored.…”
Section: Discussionmentioning
confidence: 99%